The Role of Judicial Audit in Reducing Tax Evasion Methods by Implementation of Supply Chain Management: A Field Study in the Iraqi Environment - Al-Zubaidi, Firas Khudair Abbas; Raji, Ali Abdulhussein; khudhair, Dheyaa zamil (ExcelingTech, 2019)
In the light of modern trends of financial concepts and financial developments that occurred in Iraq after 2003 and the emergence of competition between Iraqi companies listed in the Iraqi Stock Exchange for the purpose of increasing financial profits for investors and owners have led to the use of tax evasion methods by using the supply chain management systems for the purpose of increasing profits and evasion of the tax. Therefore, the focus has begun to concentrate on judicial audit role and supply chain management systems to limit the practices of tax evasion of some listed companies in the Iraqi Stock Exchange. The article has reached to a number of results, the most important of which is that there is a crucial need to apply supply chain management system in companies due to widespread phenomenon of tax evasion in Iraqi companies. Based on the study results analysis and conclusions, the researchers recommend that the General Commission for Taxes in Iraq should build a rigorous regulatory system based on judicial audit services while preserving the rights of the taxpayer, companies and the financial authority.